The challenges of retaining customers by Telekom Malaysia / Nordiyana Kamal Arriff (Faculty of Business and Management, 2008)
This study is to determine customer satisfaction towards service quality of Telekom Malaysia. From this study, we can evaluate what actually the factors that Telekom Malaysia can retain their customers and at the same time can gain competitive advantage. It consists of 5 chapters in which are completed during a period of four months. Chapter one focuses on the background of Telekom Malaysia, which consists of history of Telekom Malaysia, vision and mission statement. It is also an introduction to the study as a whole. Chapter two is the literature review, which supported this study. Many materials were used in order to relate with this study. It also emphasizes the other literatures by various authors that can be used to support this study. Research methodology and design will be discussed in chapter three. It explains how the data collection is necessary in order to gather all information related to this study. Chapter four focused on the data analysis and interpretation on this study. All findings are able to determine the customer satisfaction, which can be supported in the literature review that has been done. The accuracy of data can be determined by using the statistical approach. Last but not least, chapter five is the conclusion and recommendation, which are related with the research objective. The recommendation is made through the weakness of the findings and maybe Telekom Malaysia can use this as their references in order to improve their sales.